Production of Solvent (Acetone-Butanol-Ethanol)in Btach and Continuous Fermentation by Clostridium Saccharobutylicum Dsm 13864 Using Gelatinised Sago Starch as Substrate - Liew, Shiau Tsuey (2005)
Study on the feasibility of using improved computer-controlled HPLC and GC systems was carried out to simplify the analysis method used in solvent fermentation. The use of HPLC system with a single injection to analyse the composition of culture broth (substrates and products) during solvent fermentation was achieved by raising the column temperature to 80°C. Although good separation of the components in the mixture was achieved, a slight peak overlapped for butyric acid and acetone was observed. However, improved GC system was developed and capable to measure the products of solvent fermentation (acetone, butanol, ethanol, acetic acid and butync acid) within 22 min of d y s i s time. In order to obtain accurate quantification, GC was used to determine the products whereas HPLC was used to detect the substrates. The effect of different sago starch concentrations on solvent fermentation by Clostridium saccharohutylicum DSM 13864 was studied in anaerobic condition using 250 rnL schott Duran bottle. The optimal sago starch concentration obtained was 50 g/L where the total solvent concentration, total solvent yield and total solvent productivity were 8.97 g/L, 0.20 g/g and 0.14 g/L.h, respectively. The performance of solvent fermentation was greatly improved when 2 L stirred tank fermenter was applied using 50 g L sago starch. The fermentation time to reach the maximum total solvent concentration was shortened from 66 h to 28 k The total solvent concentration, total solvent yleld and total solvent productivity obtained was 10.89 g/L,0 .24 g/g and 0.39 g/L.h, respectively. The total solvent production in 2 L stirred tank fermenter was sigmficantly improved when glycerol was added to the medium. With the addition of 2 to 10 g!L glycerol to the medium, the production of total solvent was increased by about 3% to 50.4% as compared to fermentation without the addition of glycerol (10.89 @), respectively. Although there was a reduction in ethanol production, the production of acetone and butanol was significantly increased. Glycerol with concentration of 6 @ was optimal for improvement of the total solvent production (16.38 g/L), total solvent yield (0.35 gig) and total solvent productivity (0.59 g1L.h). From the study it was found that the condition could be adjusted to suit for acids production (high dilution rate and high pH) or solvent production (low dilution rate and low pH) by manipulating the dilution rate and culture pH of single stage continuous fermentation. The highest solvent concentration in outflow (9.10 g/L) was obtained at pH 4.5 and dilution rate of 0.05 h-*, whch gave the overall productivity of 0.46 g1L.h. However, the highest total solvent productivity (0.85 gkh) was obtained at dilution rate of 0.11 h-I at pH 4.5. Although the total solvent productivity was greatly increased in continuous culture, the final solvent concentration attained in outflow was decreased by about 53% as compared to batch culture.